Konsep Din Al-Islam Dalam Al-Qur’an (Analisis Tafsir Fi Zilal Al-Qur’an ) - Kartika, Dini; Rahmat Hidayat; Halimahtussa’diyah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The concept of din is one of the key terminologies in the Qur’an that has a complex meaning and broad conceptual implications. This study aims to analyze the concept of din al-Islam in the Qur’an based on Sayyid Qutb’s interpretation in the Fi Ẓilal al-Qur’an commentary, as well as to examine its methodological characteristics and interpretative patterns. This study uses a qualitative approach with a library research type, and applies the content analysis method to the verses of the Qur’an related to the concept of din, especially Q.S. Ali ’Imran [3]: 19. The research data comes from the Fi Ẓilal al-Qur’an commentary as a primary source and is supported by interpretation literature and scientific studies. The results of the study show that Sayyid Qutb interprets din al-Islam: Islam in question is not just a claim. In fact, Islam is submission. Islam is obedience and following. Islam is the practice of making the Book of God the law in all human affairs, and Islam is the realization of divinity and submission to God’s leadership. Islam is not understood merely as an individual ritual or formal religious identity, but as an integrative and applicable way of life. Sayyid Qutb’s interpretation is influenced by the interpretations of haraki, adabi, and ijtima’i, emphasizing the dimension of social transformation and criticism of non-Islamic systems of life. Although the interpretation of Fi Ẓilal al-Qur’an is strong in its originality of ideas and contextualization, it also has limitations, particularly in its limited reference to classical interpretations and its tendency to dichotomously interpret social reality.